2017
DOI: 10.15835/buasvmcn-vm:0006
|View full text |Cite
|
Sign up to set email alerts
|

A Metastatic Lipid-Rich Carcinoma of the Mammary Gland in a Female Cat: Clinicopathological, Histopathological and Immunohistochemical Features

Abstract: Lipid-rich invasive human breast cancer is a rare enigmatic entity among special types of infiltrating duct carcinoma. Our paper reports a lipid-rich mammary carcinoma in a female cat with the gross, microscopic and immunohistochemical description of the tumor. A 13-year-old intact adult female, mixed-breed cat was presented by the owner to the Laboratory of Pathologic Anatomy from the Faculty of Veterinary Medicine ClujNapoca, Romania. A complete necropsy examination was performed in our laboratory. The tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In the current study, most vacuolated and nonvacuolated neoplastic cells exhibited diffuse and intense cytoplasmic immunoreactivity for cytokeratin 8. This finding is similar to that obtained by Gal et al (2017).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the current study, most vacuolated and nonvacuolated neoplastic cells exhibited diffuse and intense cytoplasmic immunoreactivity for cytokeratin 8. This finding is similar to that obtained by Gal et al (2017).…”
Section: Discussionsupporting
confidence: 94%
“…Kamstock et al (2005) described the first case of lipid-rich mammary carcinoma in a 1.5-year-old female cat. Gal et al (2017) reported the second lipid-rich mammary gland carcinoma in a female cat along with a gross, microscopic, and immunohistochemical description of the tumor. Our study reported the third lipid-rich carcinoma in a 10-year-old female mixed breed cat.…”
Section: Discussionmentioning
confidence: 99%